Patrimoine juif, pouvoir marocain - Chiara Lutteri (L’Année du Maghreb)
Since the 2000s, Judaism has undergone a process of visibilization carried out by the Moroccan institutions. Its material visibility is particularly noticeable in the process of patrimonialization: the restauration of cemeteries and former Jewish neighborhoods (mellahs), the museificaiton of synagogues, the opening of museums dedicated to Jewish memory and history. This article suggests that the patrimonialization of Judaism in Morocco carries political implications that go beyond the goal of promoting Jewish history, and that touch upon the King’s role in today’s political system.Since his enthronement in 1999, the King Mohammed VI has had to face religious and political challenges (terrorist attacks in Casablanca in 2003, the 20th February Movement in 2011). These have resulted in a reconfiguration of the political powers within the Moroccan regime, sanctioned by the new Constitution of 2011. In this new political setting, the King has seen his political prerogatives formally reduced, all while striving to maintain his role of arbitrator in the Moroccan political game. The survival of the monarchical institution’s primacy centers around the King’s religious role as “commander of the faithful”. This article wishes to highlight the importance of religion in the political stability of the Moroccan monarchy. A State-sanctioned reading of interreligious history, based on peaceful coexistence and tolerance, was spread through cultural and patrimonial projects that actively participated in the survival of the King’s political centrality. The analysis focuses, first, on the creation of a nationalized memory of Moroccan Judaism. The introduction of Jewish history in Moroccan textbooks in 2020, and the project of renovation of 167 Jewish cemeteries throughout Morocco have become opportunities to underline the centrality of the monarchical institution in the survival and preservation of Jewish communities and their heritage. A closer look at the Jewish Museum of Casablanca allows us to highlight the importance of the religious dimension for the incorporation of Judaism in a new nationalist narrative. The article then focuses on Bayt Dakira, museum and cultural space located in the city of Essaouira, arguing that these sites have become symbols of a reading of history based on coexistence and proximity between Jews and Muslims, under the benevolent eyes of the sultans and kings of Morocco. Finally, this article questions the patrimonialization of Judaism and its integration in the nationalist project through the analysis of Dar Rabbi Haim Pinto in Casablanca, a non-patrimonialized site, yet an important one for the religious practice and the memory of the Casablanca Jewish community.This reflection stems from a fieldwork carried out between 2021 and 2023 with members of the Jewish community, as well as with Muslims committed to the preservation of Jewish Moroccan heritage. This fieldwork was conducted mainly in Casablanca and Essaouira, cities that host two museums dedicated to Judaism. The ecosystems of these museums constitute an entry for the analysis of patrimonial policies, and helped direct semi-structured interviews with museum personnel, and with citizens involved in the patrimonialization of Judaism in varying degrees. Moroccan newspaper articles in French and official documents published by Moroccan ministries have constituted a useful database for the understanding of how these projects have been conceived and covered. Finally, the King’s speeches, given both in Morocco and abroad, as well as some international events around the topic of Moroccan Jewish heritage helped analyze contemporary Moroccan policies directed at Jewish Moroccan heritage.